2017
DOI: 10.1186/s12906-017-1727-y
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potential of Thevetia peruviana fruit methanolic extract

Abstract: Background Thevetia peruviana (Pers.) K. Schum or Cascabela peruviana (L.) Lippold (commonly known as ayoyote, codo de fraile, lucky nut, or yellow oleander), native to Mexico and Central America, is a medicinal plant used traditionally to cure diseases like ulcers, scabies, hemorrhoids and dissolve tumors. The purpose of this study was to evaluate the cytotoxic, antiproliferative and apoptotic activity of methanolic extract of T. peruviana fruits on human cancer cell lines.MethodsThe cytotoxic activity of T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…Therefore, the un-regulated consumption of the fruits has been reported as toxic [ 5 ]. T. peruviana also produces phenolic compounds with potential usage as antimicrobial [ 6 , 7 ] and antineoplastic drugs [ 8 , 9 ]. Additionally, flavonoids have been identified in the fruits and leaves of this plant, and they are capable of inhibit the integrase enzyme and reverse transcriptase associated to DNA polymerase of the human immunodeficiency virus HIV-1 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the un-regulated consumption of the fruits has been reported as toxic [ 5 ]. T. peruviana also produces phenolic compounds with potential usage as antimicrobial [ 6 , 7 ] and antineoplastic drugs [ 8 , 9 ]. Additionally, flavonoids have been identified in the fruits and leaves of this plant, and they are capable of inhibit the integrase enzyme and reverse transcriptase associated to DNA polymerase of the human immunodeficiency virus HIV-1 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of cancer has increased to 14 million new cases and 8.2 million cancer-related deaths in 2012 (1). Cancer is characterized by the uncontrolled and invasive growth of cells (2). Chemotherapy is a traditional treatment, but chemotherapeutic drugs have many side effects (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac glycosides may be responsible for the selective cytotoxicity shown by the extracts from the leaves of Cascabela thevetia (L.) Lippold (10) and the leaves of Digitalis purpurea L. (18). We and others have previously observed that plants with cardiac glycosides, and several cardiac glycosides (e.g., digitoxin), induce potent and selective cytotoxic effects against several types of cancer cells, including lung cancer cells [11][12][13][14][15][16][17][18][19]. Isoquinoline alkaloids may participate in the cytotoxicity and selectivity observed for the extract from the bulb of Pancratium maritimum L.…”
Section: Resultsmentioning
confidence: 99%